Adaptation of commercial biomarker kits and proposal for 'drug development kits' to support bioanalysis: call for action. (22nd June 2018) - Islam, Rafiqul; Kar, Sumit; Islam, Clarinda; Farmen, Raymond
There has been an increased use of commercial kits for biomarker measurement, commensurate with the increased demand for biomarkers in drug development. However, in most cases these kits do not meet the quality attributes for use in regulated environment. The process for adaptation of these kits can be frustrating, time consuming and resource intensive. In addition, a lack of harmonized guidance for the validation of biomarker poses a significant challenge in the adaptation of kits in a regulated environment. The purpose of this perspective is to propose a tiered approach to commercial drug development kits with clearly defined quality attributes and to demonstrate how these kits can be adapted to perform analytical validation in a regulated environment.